Squeaky Cyber Buzz. - Hawkings, David (CQ Weekly, 2010)
The numbers of suspicious activities detected by the Senate's computer network security software has risen from 8 million per month in 2008 to 1.8 billion per month in 2010. This has driven home to Congress the importance of cybersecurity, which is the subject of three prominent bills, with genuine bipartisan provenance, that seek to safeguard the nation's computers and computer networks from attack. It is also the topic of the cover story in this issue of CQ Weekly.